Implementation of Content Marketing and Copywriting on the Instagram Account @vidhacoffee to Increase Brand Engagement - Sibarani, Melly Monica; Siahaan, Sabda Dian Nurani (Holistic Science, 2025)
This study aims to implement Content Marketing and Copywriting in creating captions on the Instagram account @vidhacoffee to increase brand engagement. The main problem in this study is the low level of audience interaction, as indicated by the low engagement rate before implementation. The type of research used is descriptive qualitative research, with data collection methods through observation, documentation, and distribution of questionnaires to marketing experts. The results show that after the implementation of Content Marketing and Copywriting, there was an increase in the engagement rate, from 0.22% before implementation to 4.61% after implementation. Furthermore, there was an increase in audience interaction in the comments section, indicating that implementing a copywriting strategy in caption creation can increase audience response. This increase indicates that the implementation of Content Marketing and Copywriting can increase brand engagement.